Highly‐Parallel Microfluidics‐Based Force Spectroscopy on Single Cytoskeletal Motors. Issue 18 (23rd March 2021) - Urbanska, Marta; Lüdecke, Annemarie; Walter, Wilhelm J.; van Oijen, Antoine M.; Duderstadt, Karl E.; Diez, Stefan
Abstract: Cytoskeletal motors transform chemical energy into mechanical work to drive essential cellular functions. Optical trapping experiments have provided crucial insights into the operation of these molecular machines under load. However, the throughput of such force spectroscopy experiments is typically limited to one measurement at a time. Here, a highly‐parallel, microfluidics‐based method that allows for rapid collection of force‐dependent motility parameters of cytoskeletal motors with two orders of magnitude improvement in throughput compared to currently available methods is introduced. Tunable hydrodynamic forces to stepping kinesin‐1 motors via DNA‐tethered beads and utilize a large field of view to simultaneously track the velocities, run lengths, and interaction times of hundreds of individual kinesin‐1 molecules under varying resisting and assisting loads are applied. Importantly, the 16 µm long DNA tethers between the motors and the beads significantly reduces the vertical component of the applied force pulling the motors away from the microtubule. The approach is readily applicable to other molecular systems and constitutes a new methodology for parallelized single‐molecule force studies on cytoskeletal motors. Abstract : A microfluidics‐based high‐throughput approach for the observation of cytoskeletal motor proteins under external loads is presented. DNA‐tethered beads are used as force handles to apply calibrated hydrodynamic loads on hundreds of stepping kinesin motors at a time. Their velocities, run lengths, and interaction times are measured with a throughput two orders of magnitude higher than in conventional methods.